Analysis of cash flow statements at PT. Gajah Tunggal, Tbk for the period 2018-2022 - Dewi, Maria; Basyir, Ashar; Agustiani, Rizki Muti (Junal Ilmu Manajemen, 2025)
Financial statements are reports that present a company's financial condition at a specific point in time or over a certain period. This research aims to analyze the cash flow statements of PT. Gajah Tunggal Tbk for the period 2018-2022. The research method employs quantitative data, and the type of data used is secondary data obtained from (https://www.gt-tires.com) and (https://www.idx.co.id/id). The analysis utilizes the operating cash flow ratio, capital expenditure ratio, total debt ratio, cash flow to net income ratio, and cash coverage to interest ratio. The results indicate that PT. Gajah Tunggal Tbk's financial performance, as reflected in its cash flow ratios, falls below 1 (<1) or is considered less favorable when analyzed using the operating cash flow ratio, capital expenditure ratio, total debt ratio, and cash flow coverage to interest ratio. However, the cash flow to net income ratio shows a value above 1 (>1), indicating a favorable result.